The Pro-Angiogenic Potential of Periodontal Ligament Stem Cells and Dental Pulp Stem Cells: A Comparative Analysis - Ilaria Roato; Clarissa Orrico; Sara Meinardi; Riccardo Pedraza; Alessandro Mosca Balma; Giacomo Baima; Tullio Genova; Mario Aimetti; Federico Mussano (Cells)
The role of periodontal ligament stem cells (PDLSCs) and dental pulp stem cells (DPSCs) in stimulating angiogenesis has been reported, but their angiogenetic potential has not been directly compared. In this work, paired PDLSCs and DPSCs, i.e., derived from the same donor, were tested for their immunophenotype and multi-differentiation capabilities, with particular emphasis on their pro-angiogenic activity. Flow cytometry was utilized to study the expression of mesenchymal stem cell, pericyte, and endothelial markers, while gene expression was evaluated through real-time PCR. The angiogenic potential was assessed recurring to tubulogenesis assay, co-cultures with Human Microvascular Endothelial Cell (HMEC-1), and VEGF-A quantification. The immunophenotype of DPSCs and PDLSCs was different in CD146+ and CD31+ cell subsets, but both cell types promoted HMEC-1 tubulogenesis in vitro. Consistently, VEGF-A gene expression level and its quantification in cell-conditioned media of PDLSCs and DPSCs was comparable between them, and both promoted the formation of vessel-like structures, when co-cultured with HMEC-1 cells. All together, these results showed the heterogeneity of PDLSCs and DPSCs, which are constituted of different cellular subsets, likely modulated by the microenvironmental cues. PDLSCs and DPSCs showed comparable pro-angiogenic activity, enhanced by the contemporary expression of angiogenic and chemotactic factors.